Left Supraclavicular Spindle Cell Lipoma. (25th May 2010) - Olaleye, Oladejo; Fu, Bertram; Moorthy, Ram; Lawson, Charles; Black, Myles; Mitchell, David
Abstract : Background . Spindle cell lipoma (SCL) is a benign lipomatous tumour, typically occurring in the posterior neck, shoulder or upper back of elderly males. They compose of fat, CD34 positive spindle cells, and ropey collagen on a myxoid matrix. This case highlights a rare presentation of SCL and the need for pre-operative diagnosis. Case Report . A 63-year-old gentleman presented with a pre-existing left supraclavicular mass that had recently increased in size. FNA and CT Scans were performed and results discussed in the mutidisciplinary team meeting. Excisional biopsy was recommended. Radiology . CT neck showed a left supraclavicular mass of fatty density with fine internal septations. A low-grade liposarcoma could not be excluded. Histopathology . FNA was indeterminate. Histology of specimen showed bland spindle cells with no evidence of malignancy. Immuno-histochemistry showed SCL with CD34 positivity and negative staining on CDK4 and p16. Management . Excision biopsy of the mass was performed which was technically difficult as the mass invaginated around the brachial plexus. The patient recovered well post-operatively with no neurological deficits. Conclusion . Spindle cell lipoma is a rare benign tumour and a pre-operative diagnosis based on the clinical context, imaging and immuno-histochemistry is crucial to management.